2022
DOI: 10.3390/ijerph191710768
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Infections during COVID-19 Period: Reflection of Reality or Elusive Data Due to Effect of Pandemic

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) devastated the overall health management strategy of most countries. In this scenario, the present study provided insights into the possible impact of the COVID-19 pandemic on dengue infection. This ecological study retrieved data from WHO/Government reporting system from 22 major dengue epidemic countries. Incidence of dengue infections during the pre-COVID-19 time (2015~2019) and COVID-19 period (2020~2021) was compared. A correlation between the dengue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…There was a 46% increase in dengue cases from 2015 to 2019, with a prominent peak in 2019 from Association of Southeast Asian Nations (ASEAN) region [ 19 ]. More recent studies during the pre-COVID-19 period (2015–2019) and COVID-19 period (2020–2021) showed average dengue incidences across the 22 major dengue-endemic Asian countries including Nepal and Latin American countries decreasing by 16% during the pandemic period compared to the pre-COVID-19 time (2015–2019), although sporadic increases in the incidences were observed in some countries including Singapore [ 20 ]. A few cases of COVID-19 and dengue co-infection have been reported from Nepal and other dengue-endemic countries [ 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a 46% increase in dengue cases from 2015 to 2019, with a prominent peak in 2019 from Association of Southeast Asian Nations (ASEAN) region [ 19 ]. More recent studies during the pre-COVID-19 period (2015–2019) and COVID-19 period (2020–2021) showed average dengue incidences across the 22 major dengue-endemic Asian countries including Nepal and Latin American countries decreasing by 16% during the pandemic period compared to the pre-COVID-19 time (2015–2019), although sporadic increases in the incidences were observed in some countries including Singapore [ 20 ]. A few cases of COVID-19 and dengue co-infection have been reported from Nepal and other dengue-endemic countries [ 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 Several studies indicate that during COVID-19, one of which stated that the number of dengue cases decreased by approximately 16% during the COVID-19 pandemic. 3 Reports from some ASEAN countries in 2020 followed a similar pattern: the number of dengue cases in 2020 was lower than in 2019. One of them is Indonesia, where cases were twice as high in 2019 as the previous year (137,760), while it was reported to have decreased in 2020 (95,893).…”
Section: Introductionmentioning
confidence: 88%
“…7 A recent study demonstrated a strong positive correlation between COVID-19 and dengue cases in Asian countries, underscoring the possible impact of the COVID-19 pandemic on the burden of dengue. 8 This indicates the need for greater vigilance to counter the growing dengue threat. Our commentary focuses on Singapore and highlights the lessons that can be learnt from the ongoing dengue outbreak.…”
Section: Commentarymentioning
confidence: 99%